2008
DOI: 10.1086/529385
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Renal Outcome in HIV‐Associated Nephropathy

Abstract: Whereas overall patient survival suggested an important benefit of highly active antiretroviral therapy, no additional renal benefit of early initiation of highly active antiretroviral therapy or viral suppression could be demonstrated in this large cohort of patients with established HIVAN. Severity of chronic kidney damage, as quantified by biopsy, was the strongest predictor of renal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 27 publications
4
57
2
Order By: Relevance
“…In the United States there has been a steady decline in the incidence of HIVAN with the introduction of HAART, in spite of stable frequencies of the risk variants [68] . Risk factors for progression to ESRD in HIVAN are severity of renal dysfunction, percentage of sclerotic glomeruli [25,69] , lack of viral suppression [26,70] , 2 APOL1 risk alleles [63,71] , while use of renin angiotensin system blockers were reported to be protective [25] . HIV-infected individuals with non-HIVAN pathology and two APOL1 risk alleles had an almost 3-fold risk of ESRD, in spite of effective ARTsuppression of viral load and use of renin-angiotensin aldosterone blockers; baseline kidney function was the strongest predictor of progression to ESRD in this study [71] .…”
Section: Apol1 Susceptibilitymentioning
confidence: 99%
“…In the United States there has been a steady decline in the incidence of HIVAN with the introduction of HAART, in spite of stable frequencies of the risk variants [68] . Risk factors for progression to ESRD in HIVAN are severity of renal dysfunction, percentage of sclerotic glomeruli [25,69] , lack of viral suppression [26,70] , 2 APOL1 risk alleles [63,71] , while use of renin angiotensin system blockers were reported to be protective [25] . HIV-infected individuals with non-HIVAN pathology and two APOL1 risk alleles had an almost 3-fold risk of ESRD, in spite of effective ARTsuppression of viral load and use of renin-angiotensin aldosterone blockers; baseline kidney function was the strongest predictor of progression to ESRD in this study [71] .…”
Section: Apol1 Susceptibilitymentioning
confidence: 99%
“…6,7 The pathogenesis is believed to be due to dysregulation of podocytes and tubular epithelia by HIV-1 itself. 8,9 Early identification of HIVAN is important because highly active antiretroviral therapy (HAART), corticosteroids, and inhibition of renin-angiotensin may delay disease progression 6,10,11 . Nonetheless, because HIV infection may be associated with other glomerular diseases, definitive diagnosis of HIVAN requires a kidney biopsy.…”
mentioning
confidence: 99%
“…Interestingly, the benefit of HAART on HIVAN was contradicted by one retrospective study (total 61 HIVAN with 45 biopsy-confirmed). The study demonstrated that once severe HIVAN was diagnosed, HAART and HIV viral suppression could not prevent progression towards ESRD (Post et al, 2008).…”
Section: Antiretroviral Therapymentioning
confidence: 95%